Delayed Aneurysm Rupture Following Endovascular Treatment with Contour Device: A Case Report - Osman Koc; Mostafa Mahmoud; Ehab Mahmoud; Ali Ayyad; Ahmad Own (Neurointervention)
Delayed rupture of intracranial aneurysms after endovascular treatment is a rare but serious complication. We report the first documented case of late aneurysmal rupture following treatment with a Contour intrasaccular device. A patient in their 60s with a basilar tip aneurysm underwent endovascular treatment using a 14-mm Contour device. Fifteen months later, the patient presented with a fatal intraventricular hemorrhage, and imaging revealed device displacement and aneurysm growth. This case underscores the importance of meticulous device sizing and follow-up, especially for large aneurysms.